Drugs Abuse, Law, and Society: The Role of Penitentiary Institution - Yusuf, Wahyullah A (Semarang State University Undergraduate Law and Society Review, 2021)
The problem of criminal narcotics crime has become the problem of nations and nations in the world that is always talked about. Around the world the problem of narcotics abuse is almost all the problems of nations. Narcotics abuse can certainly lead to physical damage, mental health, emotions, and attitudes in society. Problems of narcotics abuse have been threatening society and nation to become an organized crime in the national scope as well as to the international world. This study aims to analyze the problem of how the application of criminal law regarding the regulation of narcotics crime in Indonesia and how the criminal law system concerning the regulation of narcotics crime in Indonesia. Research method in scientific journal is done by normative juridical approach that is by doing analysis of problem through approach of law principles and referring to legal norms contained in legislation. The data used in this scientific journal is secondary data. This study found and emphasized that penitentiary institution has an important and strategic role on rehabilitating the drug abuse actors. However, in some cases, the penitentiary.